More second-order than ever? The 2014 European election in Portugal - Freire, A. (2015)
Considering the potential impact of the economic crisis, the main goal of the article is to ascertain whether the second-order election model lost ground in Portugal during the 2014 election to the European Parliament. We conclude that this was a more second-order contest than ever. The explanation for the resilience of the model relies on a mismatch between the citizens' growing potential for contestation and the low politicisation of European Union (EU) issues at the party level. However, the election outcomes also reveal the significance of EU issues for the radical left.